2018
DOI: 10.1093/ajcn/nqx046
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate, the oral microbiome, and cardiovascular health: a systematic literature review of human and animal studies

Abstract: Evidence for a beneficial effect in humans at risk of cardiovascular disease is limited. Furthermore, there is a need to investigate the long-term effects of dietary nitrate on cardiovascular disease clinical endpoints. Further animal studies are required to elucidate the mechanisms behind the observed effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 145 publications
4
71
1
Order By: Relevance
“…The physiological effects of inorganic nitrate consumption have received considerable research interest in recent years. Strong evidence now exists showing the potential for supplemental nitrate to reduce BP13–17 and to enhance exercise performance19–24 in healthy individuals, although evidence in clinical populations is less clear 32. This growing evidence was reflected in participant responses, with over half of participants stating that these were physiological effects of inorganic nitrate.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological effects of inorganic nitrate consumption have received considerable research interest in recent years. Strong evidence now exists showing the potential for supplemental nitrate to reduce BP13–17 and to enhance exercise performance19–24 in healthy individuals, although evidence in clinical populations is less clear 32. This growing evidence was reflected in participant responses, with over half of participants stating that these were physiological effects of inorganic nitrate.…”
Section: Discussionmentioning
confidence: 99%
“…The oral microbiome has been implicated in several oral cavity (dental caries, periodontitis, endodontic, alveolar osteitis, and tonsillitis) and systemic diseases (cardiovascular disease, stroke, pneumonia, and diabetes) [14][15][16][17]. Long et al [18] reported that several bacterial taxa in the phylum Actinobacteria are negatively associated with obesity and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary NO 3 − is well absorbed in the upper gastrointestinal tract. About 25% of dietary NO 3 − is captured by the salivary glands, where it is reduced to NO 2 − by commensal bacteria that express and secret NO 3 − -reductase enzyme in saliva [ 6 , 191 ]. The metabolic activity of the hundreds of commensal bacteria species belonging to the Granulicatella , Actinomyces , Veillonella , Prevotella , Neisseria , Haemophilus , and Rothia genera that live on the tongue can directly influence the NO 3 − to NO metabolism.…”
Section: Beetroot Product Interventions Increase Nitric Oxide Prodmentioning
confidence: 99%
“…These compounds, termed functional nutrients, provide benefits for the promotion and maintenance of human health [ 1 , 2 ]. Epidemiological studies have demonstrated that dietary nitrate (NO 3 − ) from certain vegetables can provide a physiological substrate for the production of nitric oxide (NO) which, in turn, supports cardiovascular function, causes vasodilation, and decreases blood pressure [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation